Neurofascins orchestrate assembly and maintenance of axonal domains in the central nervous system - Zonta, Barbara (The University of Edinburgh, 2008)
Close interaction between oligodendrocytes and axons is essential to initiate myelination and to form specialised domains along myelinated fibres. These domains are characterised by the assembly of protein complexes at the axon-glia interface and key components of these complexes are the Neurofascins. Neurofascins are transmembrane glycoproteins belonging to the L1 subgroup of the Immunoglobulin (Ig) superfamily of cell adhesion molecules. The Neurofascin (Nfasc) gene is subject to extensive alternative splicing. Two of the best characterised isoforms are Nfasc155 and Nfasc186, which are expressed in glia and neurons respectively. In myelinated fibres, Nfasc186 is the predominant isoform expressed at nodes of Ranvier and axon initial segments (AIS) in both the central and peripheral nervous system (CNS and PNS), whereas Nfasc155 resides on the glial side of the paranodal axoglial junction. The Neurofascin gene has been inactivated by homologous recombination and Neurofascin-null mice die within the first week of postnatal life. The main focus of this work was to investigate the role of the Neurofascins in the developing CNS. Similarly to what has been previously observed in the PNS, this study shows that in myelinated fibres of the spinal cord, nodal and paranodal markers are mislocalised and axoglial junctions do not form in the absence of the Neurofascins. In contrast to the PNS, where ensheathment of axons is unaffected, myelin proteins in the CNS are greatly reduced in the mutant. This appears to be due to the reduced ability of oligodendrocyte myelinating processes to extend along axons. This work also shows that the role of Nfasc186 is to maintain the long term stability of the AIS rather than its assembly. In the PNS, Nfasc186 was found to play an essential role in node assembly. However, PNS and CNS nodes are likely to assemble by different mechanisms. To investigate the relative contribution of the Neurofascin isoforms in CNS node assembly, this work made use of transgenic lines in which either neuronal Nfasc186 or glial Nfasc155 was expressed on a Neurofascin null background. Expression of either isoform was found to independently rescue the nodal complex and a model of how the Neurofascins cooperate in the assembly of the CNS node of Ranvier is proposed.
The Neurofascins orchestrate assembly and maintenance of axonal domains in the central nervous system
Keywords: neurofascin; myelination; nodes of ranvier